MODELING INNOVATIONS IN PUBLIC ADMINISTRATION - Ragozin, Yurii (Public Management and Policy, 2025)
The article examines the problem of modeling innovations in public administration as a strategic tool for increasing the efficiency of the public sector under modern challenges. The relevance of the research is explained by the necessity for state institutions to quickly adapt to globalization, Ukraine’s European integration, digital transformation, and crisis phenomena caused by war, the pandemic, and economic fluctuations. The theoretical basis of the study includes the definition of the concept of “innovation” in the field of public administration, as well as the analysis of domestic and international approaches to its modeling. The purpose of the research is to systematize key methods of innovation modeling and evaluate their significance for shaping effective state policy. The methodology is based on the application of systemic, simulation, scenario, and expert approaches, which allow taking into account the multifactorial nature of management processes and predicting the consequences of decisions. The findings indicate that the systemic approach provides a holistic vision of innovation processes, simulation modeling makes it possible to test different scenarios in a virtual environment, the scenario method creates conditions for forecasting alternative development trajectories, and expert assessments help integrate qualitative factors that are difficult to formalize. Particular attention is paid to the Ukrainian context, where the combination of digitalization, the need for transparency, and the deficit of public trust form specific challenges for the implementation of innovations. The conclusion emphasizes that effective modeling of innovations is a necessary condition for Ukraine’s transition to the concept of “smart governance,” based on transparency, accountability, and citizen orientation. The results of the study may be used for developing strategies of public administration modernization, evaluating reforms, and shaping innovation policy at all levels of government.